DEFINING AND DIFFERENCIATING THE TERMS LINGUODIDACTICS AND METHODOLOGY (Scientific journal of the Fergana State University, 2024)
This article is devoted to the analysis of the term linguodidactics, its importance in language teaching and learning, the goals and tasks of the science, and the opinions of various scientists.